Article 12 of the UN Convention on the Rights of the Child and the Understanding of the Committee on the Rights of the Child - Benyusz , Márta (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:The current book chapter provides an in-depth analysis of Article 12 of the United Nations Convention on the Rights of the Child, which is the very basis of children’s fundamental right to participate. It focuses on the legal analysis of Article 12 and the understanding and approach that is elaborated by the Committee on the Rights of the Child. Besides the analysis of Article 12, it provides an outline of the approach that shall be taken when implementing Article 12 in any life setting. Keywords: children’s rights, the child’s right to be heard, the child’s right to express views, genuine participation, United Nations Convention on the Rights of the Child, best interest of the child, capability of forming his or her views, practical implementation, consultative process, participation process, self-advocacy